1999
DOI: 10.1073/pnas.96.15.8675
|View full text |Cite
|
Sign up to set email alerts
|

JE-2147: A dipeptide protease inhibitor (PI) that potently inhibits multi-PI-resistant HIV-1

Abstract: We designed, synthesized, and identified JE-2147, an allophenylnorstatine-containing dipeptide HIV protease inhibitor (PI), which is potent against a wide spectrum of HIV-1, HIV-2, simian immunodeficiency virus, and various clinical HIV-1 strains in vitro. Drug-resistant clinical HIV-1 strains, isolated from seven patients who had failed 9-11 different anti-HIV therapeutics after 32-83 months, had a variety of drug-resistance-related amino acid substitutions and were highly and invariably resistant to all of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 20 publications
3
153
0
Order By: Relevance
“…5). These findings are consistent with the known mode of action of JE2147, which has been shown to block release of mature HIV virions from infected cells, but does not inhibit release of HIV gp120 secreted in the form of immature defective virions (24). The latter process is mediated by a cellular protease and thus is not affected by drugs that impair function of the HIV protease.…”
Section: Hiv Gp120 Is Produced and Secreted By DC In The Presence Of supporting
confidence: 87%
See 1 more Smart Citation
“…5). These findings are consistent with the known mode of action of JE2147, which has been shown to block release of mature HIV virions from infected cells, but does not inhibit release of HIV gp120 secreted in the form of immature defective virions (24). The latter process is mediated by a cellular protease and thus is not affected by drugs that impair function of the HIV protease.…”
Section: Hiv Gp120 Is Produced and Secreted By DC In The Presence Of supporting
confidence: 87%
“…Zidovudine and didanosine (ddI) were purchased from Sigma-Aldrich (St. Louis, MO) and JE2147 was obtained from Japan Energy (Tokyo, Japan). The latter is a relatively new potent protease inhibitor that has been used in previous laboratory studies (24,25). Dr. R. Offord at the University of Geneva (Geneva, Switzerland) kindly provided aminooxypentane (AOP)-RANTES, Dr. N. Fujii at Kyoto University (Kyoto, Japan) kindly provided AMD3100, and Genentech (Vacavill, CA) kindly provided soluble (s) CD4.…”
Section: Reagentsmentioning
confidence: 99%
“…The wild-type infectious clone, HIV-1 WT , produced by COS-7 cells transfected with pHIV-1 NL4-3 was propagated in human CD4 ϩ MT-2 or H9 cells in the presence of increasing concentrations of an antiretroviral agent as described previously (4,14,16). Briefly, MT-2 or H9 cells (5 ϫ 10 5 ) were exposed to wild-type HIV-1 1NL4-3 and cultured in the presence of each PI at initial concentrations of 0.0005-0.03 M. When the virus began to propagate in the presence of the drug, the drug concentration was increased.…”
Section: Generation Of Hiv-1 Variants Resistant To Pis-mentioning
confidence: 99%
“…This selection was carried out for a total of 27-80 passages. For the generation of JE-2147-resistant virus, an infectious clone carrying I84V substitution in the protease (HIV-1 I84V ) was employed instead of HIV-1 WT (14). Proviral DNA in the lysates of HIV-1-infected cells of the last passage was sequenced as indicated (4).…”
Section: Generation Of Hiv-1 Variants Resistant To Pis-mentioning
confidence: 99%
“…HIV A02 was initially isolated at the National Institutes of Health Clinical Center from a treatment-experienced male patient (age 44 years) who had been heavily treated with the PIs IDV, RTV, and SQV, along with reverse transcriptase (RT) inhibitors abacavir (ABC), 3=-azido-2=-dideoxythymidine (AZT), 2=,3=-dideoxyinosine (ddI), 3=-thiacytidine (3TC), 2=,3=-dideoxycytidine (ddC), and 2=,3=-didehydro-2=,3=-dideoxythymidine (d4T), as a part of 39-month antiviral therapy (10). Antiviral assays with viral isolates obtained by culturing the peripheral blood mononuclear cells (PBMCs) from the patient's blood sample showed 4-to Ͼ5,000-fold-increased resistance against IDV, RTV, SQV, and the RT inhibitors mentioned above (10). In the present study, the antiviral assays showed that both GRL008 and DRV, which contain the bis-THF group as the P2 moiety, were highly active with a desirable genetic barrier against HIV A02 , with no significant change in their EC 50 s against HIV A02 compared to those against HIV WT .…”
Section: Discussionmentioning
confidence: 99%